THE SERBIAN FUNCTIONAL FOOD MARKET: DOES REGULATION MAKE A DIFFERENCE? - Žaklina, Stojanović; Radmila, Dragutinović-Mitrović (Economic Annals, 2012)
This paper focuses on empirical analysis of the Serbian functional food market and its comparison with those in other Western Balkan countries (WBC). The purpose is to examine whether the existence of regulation, as an institutional precondition, makes a difference on the operating of the functional food market. This market is a new, fast developing segment, based on health claims made for food. Consumers in Serbia cannot verify health claims either before or after the purchase/consumption, since the property rights on information are extremely weak. Additionally, with successful innovation the free-rider problem usually occurs. Thus, strong institutional support is necessary to ensure regular market functioning. In order to identify the effects of regulation and some other factors with crucial influence on the differences between Serbian and other WBC functional food markets, pooled cross sectional analysis is conducted. The fixed-group effects model is estimated based on data of product categories observed across WBC. Differences in the current level of WBC market development could be explained by the existence of legal regulation, competition, and other factors. All results implicate the necessity of regulatory supervision as well as closer cooperation between government, the private sector, consumer groups, academics, and the research community in further functional food market development in Serbia.